How aging process changes characteristics of vehicle emissions? A review. Issue 17 (1st September 2020) - Liu, Huan; Qi, Lijuan; Liang, Chunsheng; Deng, Fanyuan; Man, Hanyang; He, Kebin
Abstract: With increasing road and non-road vehicles in use, air quality and human health have been under greater pressure in recent years. Generally, changes involving aerosol-based vehicular pollutants are aging processes, which can alter vehicle emissions to varying degrees. We summarize the effects of the aging process on vehicle emission characteristics in this review. The initial statuses of the hygroscopicity, size distribution, phase partitioning, morphology, and chemical composition of vehicle emissions are described. Changes in these properties are produced by a series of actions, including physical means and photochemical reactions, which are characterized by the organic aerosol (OA) atomic ratio and mass spectra. Moreover, the vehicle driving cycle, after-treatment technologies and fuels affect these properties in various ways. The key driving forces of the aging mechanism of vehicle emissions mainly include diffusion, phase partitioning, and organic gas oxidation. Future research requirements to support vehicle-related air pollution control are also discussed, involving topics such as cloud condensation nuclei (CCN) and ice nucleation (IN) of aged diesel particles, reacting phases, unknown precursors or formation pathways, aged OA and source appointment, and emission controls. To what degree the aging process changes vehicle emission properties needs further study.